DC shunt motor speed control methods using MATLAB/Simulink and interfaced with graphic user interface (GUI) / Muhammad Najmi Hamzah - Hamzah, MMuhammad Najmi (2010)
This thesis presents simulation model of DC shunt motor speed control method using MATLAB/Simulink software and interfaced with Graphical User Interface (GUI) software. In this thesis, DC shunt motor speed is controlled by armature resistance, field resistance and armature voltage speed control. Its steady state torque-speed characteristics are observed and analyzed. The simulation model will enable an easier understanding for undergraduate electric machinery courses on how the actual machines work. MATLAB/GUI was incorporated in the project to display results obtained. MATLAB/GUI is user friendly and a very helpful tool to determine the speed changes of DC shunt motor.